The Effect of Grapevine Age (Vitis vinifera L. cv. Zinfandel) on Phenology and Gas Exchange Parameters over Consecutive Growing Seasons - Vegas Riffle; Nathaniel Palmer; L. Federico Casassa; Jean Catherine Dodson Peterson (Plants, 2021)
Unlike most crop industries, there is a strongly held belief within the wine industry that increased vine age correlates with quality. Considering this perception could be explained by vine physiological differences, the purpose of this study was to evaluate the effect of vine age on phenology and gas exchange parameters. An interplanted, dry farmed, Zinfandel vineyard block under consistent management practices in the Central Coast of California was evaluated over two consecutive growing seasons. Treatments included Young vines (5 to 12 years old), Control (representative proportion of young to old vines in the block), and Old vines (40 to 60 years old). Phenology, leaf water potential, and gas exchange parameters were tracked. Results indicated a difference in phenological progression after berry set between Young and Old vines. Young vines progressed more slowly during berry formation and more rapidly during berry ripening, resulting in Young vines being harvested before Old vines due to variation in the timing of sugar accumulation. No differences in leaf water potential were found. Young vines had higher mid-day stomatal conductance and tended to have higher mid-day photosynthetic rates. The results of this study suggest vine age is a factor in phenological timing and growing season length.